EFFECT OF TAPIOCA FLOUR ADDITION TO VARIOUS LEVELS OF QUALITY BEEF MEATBALLS - Levi, Herodion Pita (Jurnal Sains Peternakan, 2014)
This research was conducted to determine the effect of the amount of tapioca flour mixture to the quality of beef meatballs. This study used a complete randomized design with one factor, namely the amount of tapioca flour Â (T): (20% 30% 40% and 50%). The parameters analyzed were the degree of acidity and value organoleptic (color, flavor and firmness). The results showed that the addition of various levels of different starch towards making meatballs can produce the same pH that is 5.5 whereas the normal pH is 7.0, which means the acidity level is still below standard. In the organoleptic tests it can be concluded that the addition of starch at various levels in the making meatballs there is no real effect on the taste and aroma, while the color and texture of the tapioca flour at the level of 40% and 50% there is a very real difference effect.Keywords : The meatballs and tapioca ingredient